Organic carbon analyses of Van Veen grab samples from Baker River and Baker-Martinez Fjord - Sophie Hage; Sébastien Bertrand; Benjamin Amann; Brian Reid; Elke Vanderkerkhove (PANGAEA, 2025)
This dataset presents bulk organic geochemical data (TOC, d13C) obtained by EA-IRMS analysis on surface fjord sediment at the mouth of Baker River in the Baker-Martinez Fjord system, Chilean Patagonia (44-48?S). The samples were collected in February 2017 using a Van Veen grab sampler.